Pneumococcal vaccination coverage and willingness in mainland China - Shao, Weihao; Chen, Xiaorui; Zheng, Caifang; Wang, Gaili; Zhang, Bowen; Zhang, Weidong (Tropical medicine & international health, 2022)
Objectives To estimate the coverage and willingness of pneumococcal vaccination and further explore the influencing factors of vaccination willingness among people in mainland China. Methods Literature searches were conducted independently by two researchers in English‐ and Chinese‐language databases from database inception to 6 October 2021. A random‐effects meta‐analysis model was used to derive summary vaccination coverage and willingness. Predefined subgroup analysis and meta‐regression were performed to explore the sources of heterogeneity. Results A total of 97 studies were included in this meta‐analysis. The summary vaccination coverage in 76 included studies was 21.7% (95% confidence interval [CI]: 17.2%–26.5%). Subgroup analysis shows that the summary coverage was 29.0% (95% CI, 20.4%–39.1%) among the permanent residents and 20.7% (95% CI, 12.4%–35.9%) among the floating residents. The eastern and central regions presented higher coverage than the western region. Notable differences were observed between the various study populations. A total of 27 studies provided an estimation of vaccination willingness, with a summary willingness of 51.2% (95% CI, 40.4%–61.9%). In subgroup analysis, the summary willingness was 57.9% (95% CI, 48.3%–67.2%) in urban areas and 52.3% (95% CI, 40.8%–63.8%) in rural areas. Parents with children and people with a history of pneumonia were more willing to be vaccinated than the elderly. Recommendations by family members and physicians, previous pneumococcal and influenza vaccination, perceived vaccination effectiveness and severity of disease and a history of pneumonia contributed to vaccination willingness. Conclusions Compared to global estimates and other countries, pneumococcal vaccination coverage and willingness are at a lower level in mainland China. Recommendations for vaccination by family members and doctors, a history of vaccination and the perception of pneumonia and vaccination are associated with greater willingness to be vaccinated.